2013
DOI: 10.1007/s12012-013-9202-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiohemodynamic and Electrophysiological Effects of Anti-influenza Drug Oseltamivir In Vivo and In Vitro

Abstract: Electropharmacological effects of oseltamivir were studied in comparison with pilsicainide using halothane-anesthetized dogs (n = 4) and isolated left atrium of guinea pigs (n = 5). Oseltamivir (0.3, 3 and 30 mg/kg, i.v.) or pilsicainide (1 and 3 mg/kg, i.v.) was additionally administered to the dogs. The low dose of oseltamivir provided clinically relevant plasma concentrations with C max of 4 μM. The low and middle doses of oseltamivir increased cardiac output, whereas the middle dose increased blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…Based on our previous knowledge with the halothane-anesthetized canine model (Kise et al, 2010;Kitahara et al, 2013;Yamazaki-Hashimoto et al, 2015), the peak plasma concentration after the administration of 1, 10 and 100 mg/kg/10 min of a drug could be estimated to be approximately 1, 10 and 100 μg/mL, respectively. Mean- while, the peak plasma concentration of vidarabine after the intravenous administration in a dose of 10 mg/kg for 3 hr to healthy human subjects has been shown to be 0.2 μg/mL (0.75 μM) in the interview form from the manufacturer.…”
Section: Rationale For the Drug Doses Assessedmentioning
confidence: 99%
“…Based on our previous knowledge with the halothane-anesthetized canine model (Kise et al, 2010;Kitahara et al, 2013;Yamazaki-Hashimoto et al, 2015), the peak plasma concentration after the administration of 1, 10 and 100 mg/kg/10 min of a drug could be estimated to be approximately 1, 10 and 100 μg/mL, respectively. Mean- while, the peak plasma concentration of vidarabine after the intravenous administration in a dose of 10 mg/kg for 3 hr to healthy human subjects has been shown to be 0.2 μg/mL (0.75 μM) in the interview form from the manufacturer.…”
Section: Rationale For the Drug Doses Assessedmentioning
confidence: 99%
“…However, in basic studies, pilsicainide was shown to block also the K + channels. Pilsicainide blocks the K + channel current in the human ether‐a‐go‐go‐related gene (HERG) with a preferential affinity for the open state of the channel, and shows a fast access to the binding site [18–20]. As a result, the K + channel blocking action of pilsicainide prolonged the QTc interval in patients presenting with very high pilsicainide concentrations.…”
Section: Discussionmentioning
confidence: 83%
“…Oseltamivir is fairly cardio-benign, and in fact in animal models has been shown to reduce the risk of atrial and ventricular arrhythmias. 22,23 Anti-malarial Drugs Chloroquine, a widely used anti-malarial and autoimmune disease drug, has recently been reported as a potential broad-spectrum anti-viral drug. 24,25 Chloroquine is known to block virus infection by increasing the endosomal pH required for virus/cell fusion and interfering with the glycosylation of cellular receptors of SARS-CoV.…”
Section: Investigational Therapies and Cardiac Concerns Anti-viral Drugsmentioning
confidence: 99%